PEMAKAIAN PUPUK ALAM BERBAHAN BAKU ZEOLIT DAN KOMPOS PADA BUDIDAYA TANAMAN CABAI (CAPSICUMFRUTESCENS) - ONGKO CAHYONO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2015)
This study aimed to assess the dose of zeolite plus organic compost and inorganic fertilizer on yield of chili pepper (Capsicum frutescens L). This study was conducted fromApril â€“ July, 2012 in the Laboratory of Soil Science and in the glass house of Faculty of Agriculture UTP Surakarta, and was done under factorial design which was arranged in randomized completely design (CRD) consisting of two factors (doses of zeolite and doses of inorganic fertilizers) and three replications. The study concluded that the use of zeolit+organic compost increased yield of chili pepper significantly.Â Application of zeolit+organic compost as much as 500 kgs ha-1 and 1000 kgs ha-1 increased significantly the weigth of fruit at every level of inorganic fertilizer.Â By applying one half of dose of inorganic fertilizer, the treatment of 500 kg ha-1 of zeolit+compost yielded chili fruit as high as 141.67 grams per plant; and the treatment of 1000 kg ha-1 of zeolit+compost yielded chili fruit as high as 140 grams per plant. Those yield was not significant to the control treatment, which was as high as 141 grams per plant. Therefore it could be concluded that the application of zeolit+compost under doses of 500 kg ha-1 and 1000 kg ha-1 could reduce the use of inorganic fertilizer up until 50 percent.